ITRAQ‐based proteomics of sunflower cultivars differing in resistance to parasitic weed Orobanche cumana. Issue 13 (July 2017) - Yang, Chong; Xu, Ling; Zhang, Na; Islam, Faisal; Song, Wenjian; Hu, Luyang; Liu, Dan; Xie, Xiaonan; Zhou, Weijun
Abstract : Orobanche cumana is an obligate root parasite causing severe damage to many economically important crops, including sunflowers worldwide. For efficient control measures, it is necessary to understand the resistant mechanism during interaction at molecular level. The present study emphasizes on comparative proteomics to investigate the mechanistic basis of compatible and incompatible interaction of O. cumana with resistant (JY207) and susceptible (TK0409) sunflowers. More than 3500 proteins were identified from two cultivars by iTRAQ analysis. Identified proteins associated with general functions, posttranslational modification, energy production and conversion, carbohydrate transport and metabolism, and signal transduction mechanisms were the most represented category of induced proteins in both cultivars. The resistant interaction was characterized by alteration of defense‐related proteins involved in recognition of parasites, accumulation of pathogenesis‐related proteins, biosynthesis of lignin, and detoxification of toxic metabolites in JY207 after inoculation. The susceptible interaction was characterized by decreased abundance of proteins involved in biosynthesis and signaling of plant growth regulators including auxin, gibberellin, brassinosteroid, and ethylene in TK0409 after inoculation. The present study provides comprehensive details of proteins and differential modulation of pathways regulated under compatible and incompatible interaction, allowing the identification of important molecular components for development of sustainable resistance against this parasite.